2009
DOI: 10.1051/vetres/2009060
|View full text |Cite
|
Sign up to set email alerts
|

Time course differential gene expression in response to porcine circovirus type 2 subclinical infection

Abstract: This study was aimed at characterizing the potential differences in gene expression in piglets inoculated with Porcine circovirus type 2 (PCV2), the essential causative agent of postweaning multisystemic wasting syndrome. Seven-day-old caesarean-derived, colostrum-deprived piglets were distributed into two groups: control (n = 8) and pigs inoculated with 105.2 TCID50 of the Burgos PCV2 isolate (n = 16). One control and three inoculated pigs were necropsied on days 1, 2, 5, and 8 post-infection (p.i.). The rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…Consistent with our findings are earlier results for the pig [17], [29] and studies of murine spleen lumphocyctes [25], [28] that found differential expression of genes involved in both immune response and processes of cell signaling, cellular and organismal growth, cell cycle control, apoptosis, cytoskeleton organization, biosynthesis, metabolism as well as stress, toxicology response and oncogenesis or tumor suppression.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our findings are earlier results for the pig [17], [29] and studies of murine spleen lumphocyctes [25], [28] that found differential expression of genes involved in both immune response and processes of cell signaling, cellular and organismal growth, cell cycle control, apoptosis, cytoskeleton organization, biosynthesis, metabolism as well as stress, toxicology response and oncogenesis or tumor suppression.…”
Section: Discussionsupporting
confidence: 93%
“…For example, the same phenomenon was observed upon macrophage exposure to tobacco smoke, wherein the expression of TLR3 was increased and severe inflammation was observed after treated with TLR3 ligand [32]. Reverse: AAACGGCAAACACCATCCAAAGT a from reference [21], b from reference [22], c from reference [9].…”
Section: Toll-like Receptorsmentioning
confidence: 60%
“…Previous studies have investigated the cytokine and chemokine gene expression profile of PMWS by transcriptomic and genomic analyses. For example, the cytokine mRNA expression profile in lymph nodes of PMWS pigs was reported [17], as was the global transcriptome profile of colostrums-deprived piglets experimentally infected with PCV2 [18,19]. The genomic expression profile in lymph nodes of lymphoid-depleted PCV2-infected pigs was also reported [20].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the second deviating gene signature originates from pigs that were subclinically infected with PCV2 (Fig 2A, arrow). Unlike S. Typhimurium , this cannot be explained by pathogen clearance since these experimentally PCV2-infected pigs remained viremic throughout the original study [19]. Instead, pathogen-distressed host responses appear here to be repressed in lymph nodes with low-level subclinical PCV2 replication.…”
Section: Resultsmentioning
confidence: 95%